(untitled) (Abingdon, UK, 2007)
This fully updated edition of Redesigning English explores the innovative uses of English from early manuscripts to post-colonial literature, creative writing and developments in new media. Focusing on how English has, and continues to evolve through its global status, there is a strong emphasis on the visual forms of language and communication, and on issues of identity and politics.
Keywords: English language,English language,English language,English language; History,Reform,Technical English,Social aspects